"Don't hate me because I'm a foreigner": Historical and narrative analyses of Western expatriates' experiences in Singapore. (2016) - McNulty, Yvonne
I examine the impact of foreign talent policy relative to the experiences of Western expatriates in Singapore. I frame the debate by examining the rise and fall in public opinion about Singapore's foreign talent policy, the resulting 'negotiated power struggle' that has arisen between the Singapore government and its citizens stemming from the influx of skilled foreigners since 2005, and the government's strategic response to the 7, 000 multinational corporations (MNCs) that operate in Singapore relative to their global staffing strategies for the next decade, and beyond. Findings illustrate that, despite assumptions to the contrary and while also retaining strong allegiances to their countries of origin, many Western expatriates in Singapore: 1) live 'locally' alongside their Singaporean neighbours; 2) appreciate and welcome the functioning of the city state; 3) make deliberate choices to be in, and integrate within, Singapore to contribute to the economic development of the city.